Electoral Fairness in South Asian Democracy: Exploring the Role of Media and Civil Society - Md. Shah Jalal; Mostafizur Rahaman; Rajib Chandra Das (CV Projurnal Mitra Publikasi, 2025)
In South Asia, media and civil society play a complementary and significant role in the electoral context. This study aims to evaluate the role of media and civil society in ensuring electoral democracy in the Indian sub-continent by comparing relevant legal mechanisms. It employs a doctrinal legal research method for systematic review of laws and policies of the selected countries to substantiate the doctrinal approach of electoral democracy. In this qualitative research the authors have tried to understand the various actors of election and fairness. The media and civil society significantly contribute to checking electoral engineering, among other things. In democracy election is a campaign, a competition and source of political rivalry which is highly motivated from the role of the media and civil society. Lack of institutional clarity, administrative accountability, and effective role of media, electoral deviations are committed. Recently, it has been observed that non-formal sources of media also perform significant role during the electoral process. It suggests that the development of electoral democracy in the Indian subcontinent could not be handled properly unless there are uniform media norms based on information about electoral conspiracy, vandalism, and human rights violations, etc. whereas the perpetrator might be influenced by the techniques that apply in a country.